Health perception and healthy lifestyle behaviors in factory workers - (:unkn) unknown (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2018)
Objective: The aim of this study was to determine healthy lifestyle behaviors and health perception of the factory workers. Material and Methods: This study is a descriptive research. The population of this research was composed of people working in two different privatelyowned factories in the city of Kocaeli/Gebze. The study was conducted between dates 1-31 May 2016. It was aimed to include total workers without sampling, so the number of study population was 356. However, study was completed with 221 voluntary workers. The workers were informed about the study, and their consents were provided. Data were collected by using sociodemographic characteristics form, a questionnaire form encompassing health-related characteristics, Healthy Lifestyle Behaviors Scale II, and Health Perception Scale. Results: The average age of workers was 32.41 +/- 9.27 years, 76.0% of them were males, 59.3% were married, 50.7% had no children, 41.2% were graduated from a university, and 37.1% were working for at least 4 years. Of participants, 42.5% were smoking, and 37.1% were taking alcohol. The mean Healthy Lifestyle Behaviors Scale II was determined 130.70 +/- 21.98 points, and the lowest point in subscale was determined in physical activity, whereas the highest point was determined in spiritual development. The mean of Health Perception Scale was 39.84 +/- 8.29 points, and the lowest point in subscale was determined in importance of health, whereas the highest in control center. As the result, marital status, and education level of workers had impacts on healthy lifestyle behaviors. Individuals who were married and had children performed more physical activity. It may be useful to provide training and counseling services that raise awareness about healthy lifestyle behaviors in workplaces by occupational physicians, and nurses.
Keywords: Factory; worker; healthy lifestyle behavior; health perception; OCCUPATIONAL-HEALTH; PROMOTING BEHAVIORS